Model Pemanfaatan Koleksi Digital dalam Memenuhi Kebutuhan Informasi Oleh Siswa di Perpustakaan SMA Negeri 5 Bukittinggi - Rizky, Hafiz (Universitas Negeri Padang, 2022)
This research examines how to use digital book collections in meeting information needs by students at sma Negeri 5 Bukittinggi Library. The purpose of this research is to find out the model of utilizing digital book collections in meeting students' information needs and to find out the fulfillment of students' information needs by utilizing digital book collections at the SMA Negeri 5 Bukittinggi Library. The method used is descriptive kuantitatif. The population of this study is all students of SMA Negeri 5 Bukittinggi in the 2021-2022 school year with a sample of 92 respondents. The sampling technique in this study used random sampling techniques. Research instruments use questionnaires as the main data. Test analysis requirements using validity tests and reliability tests. The data analysis technique used is calculations using the mean to calculate the average of values, grand mean calculations are used to calculate the total number of averages of each individual or variabel. The results of this study show that the utilization model consisting of 3 models, namely, the process of utilizing digital book collections is in a very high category, the utilization rate of digital book collections is in a high category, and factors that affect the utilization of digital book collections are in a very high category. In the SMA Negri 5 Bukittinggi Library, this digital book collection utilization model is a model to meet students' information needs such as cognitive needs that are in a very high category, affective needs are in the high category, and personal integration needs are in the high category, which is the result of using digital book collections at SMA Negeri 5 Bukittinggi Library.